Regulation and Implications of the Electronic Notary and Remote Notary Concepts under Indonesian Positive Law - Rahayu Sri Utami; Yesi Rahman Sari (Greenation Research & Yayasan Global Resarch National, 2026)
The rapid development of information technology has encouraged the digitalization of legal services, including notarial practice through the concepts of electronic notary and remote notary. This study aims to analyze the regulation of these concepts within the Indonesian legal system and examine their implications for legal certainty, deed authenticity, personal data protection, and notarial practice. This research employed a normative legal method using statutory, conceptual, and comparative approaches. Legal materials were collected through library research and analyzed qualitatively. The results indicate that neither the electronic notary nor the remote notary has a comprehensive legal basis in Indonesia. Existing regulations continue to require the physical presence of the parties, direct reading of the deed, and handwritten signatures as essential elements of an authentic notarial deed. Although electronic documents are generally recognized under Indonesian law, notarial deeds remain excluded from such recognition. Consequently, deeds executed electronically risk losing their status as authentic deeds and may create legal uncertainty. This study concludes that implementing electronic and remote notary services requires amendments to the Law on Notary Position and the formulation of clear technical regulations that accommodate technological developments while preserving the authenticity of deeds and ensuring legal protection for all parties.